Explaining Returns with Cash-Flow Proxies - Hecht, Peter; Vuolteenaho, Tuomo (Review of Financial Studies, 2006)
Stock returns are correlated with contemporaneous earnings growth, dividend growth, future real activity, and other cash-flow proxies. The correlation between cash-flow proxies and stock returns may arise from association of cash-flow proxies with one-period expected returns, cash-flow news, and/or expected-return news. We use Campbell's (1991) return decomposition to measure the relative importance of these three effects in regressions of returns on cash-flow proxies. In some of the popular specifications, variables that are motivated as proxies for cash-flow news also track a nontrivial proportion of one-period expected returns and expected-return news. As a result, the R-super-2 from a regression of returns on cash-flow proxies may overstate or understate the importance of cash-flow news as a source of return variance. Copyright 2006, Oxford University Press.